Mandatory multidisciplinary approach for the evaluation of the lymph node status in rectal cancer - Marian Diaconescu; Cosmin V. Obleaga; Cecil S. Mirea; Mihai C. Ciorbagiu; Emil Moraru; Ionica D. Vilcea (Journal of Mind and Medical Sciences)
Colorectal cancer is the third most frequently reported malignancy and also the third leading cancer-related cause of death worldwide. Lymph node evaluation, both preoperatively and postoperatively, represents an important aspect of the diagnosis and therapeutic strategy in colorectal cancer, such that an accurate preoperative staging is required for a correct therapeutic strategy. Treatment of rectal cancer with positive lymph nodes, a very important predictive prognostic parameter, is currently based on neoadjuvant chemoradiotherapy followed by total/ surgical mesorectal excision and adjuvant regimen.